2020
DOI: 10.1021/acs.langmuir.0c01050
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement Effect on Surface Tension: Perspectives from Molecular Potential Theory

Abstract: Liquid–vapor surface tension (ST) in nanopores attracts great attention in many industries because of the prosperity of nanoscience and nanotechnology. Here, considering the important emerging new physical phenomena induced by nanoconfinement effects, including curvature-dependent and shift-critical temperature (T c)-dependent effects, the anomalous variation of ST in nanopores is captured from the molecular potential perspective. Furthermore, a simple analytical model is proposed to determine the ST in nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…According to their results, complex interactions of pore morphology and wettability would be a significant controlling parameter for the displacement efficiency, both in heterogeneous and homogenous porous media [39]. Feng et al (2020) considered that the non-confinement influence contained a shift critical temperature and curvature dependent effect on nanopores. They found that the non-confinement effect on the nanometer pore sizes (it would be more sensitive especially with a decrease in pore sizes) had reduced the surface tension [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their results, complex interactions of pore morphology and wettability would be a significant controlling parameter for the displacement efficiency, both in heterogeneous and homogenous porous media [39]. Feng et al (2020) considered that the non-confinement influence contained a shift critical temperature and curvature dependent effect on nanopores. They found that the non-confinement effect on the nanometer pore sizes (it would be more sensitive especially with a decrease in pore sizes) had reduced the surface tension [40].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2020) considered that the non-confinement influence contained a shift critical temperature and curvature dependent effect on nanopores. They found that the non-confinement effect on the nanometer pore sizes (it would be more sensitive especially with a decrease in pore sizes) had reduced the surface tension [40].…”
Section: Introductionmentioning
confidence: 99%
“…Where is the disjoining pressure of water film on flat surface, Pa; is potentials of the solid-water and water-gas interfaces respectively, V; is the 𝑘 coefficient for the strength of structural force, N/m 2 ; the characteristic length of 𝜆 water molecules, m. The values of these parameters are displayed in Table 1 with reference to previous work [43] . Here, we assumed interfacial tension as a constant value, and its dependence [44,45] on other variables will be included in our future work. As shown in this table above, the thickness of water film is a function of pore radius and humidity.…”
Section: Water Distribution Characteristicmentioning
confidence: 99%
“…46−49 Generally, the elements of the confinement effect are imbedded into the EOS for the phase equilibrium calculation of fluids in nanoscale domain, among which the IFT is determined by coupling the parachor model with the EOS model. 1,4 For example, Yang et al extended the classical PR EOS for unconventional reservoir fluids by incorporating critical property shift and capillary pressure, while the IFT was calculated by the extended parachor model. 46 Therefore, this kind of method is not accurate enough both for the IFT and the phase equilibrium estimation because the parachor model is empirical and does not take the confinement effect into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…As a prime parameter in basic formulations of many processes, including nucleation, imbibition, etc., IFT has attracted great attentions due to its wide and practical applications, such as chemical reactions, energy storage, heterogeneous catalysis, biological membrane operations, and in particular, oil and gas productions in conventional/unconventional reservoirs. When the pore size is on the nanoscale, the confinement effect becomes strengthened, and the thermodynamic properties and interfacial behavior of nanoconfined fluids are quite different from that of the bulk counterparts. Therefore, macroscopic expressions of the IFT cannot be employed directly, and the influences of curvature and wall–fluid interaction must be considered in theoretical studies.…”
Section: Introductionmentioning
confidence: 99%